How to Implement Strategic Foresight (and Why) - Behar, Alberto (IMF How To Notes, 2021)
This note explains the value of strategic foresight and provides implementation advice based on the IMF's experience with scenario planning and policy gaming. Section II provides an overview of strategic foresight and some of its tools. Scenario planning and policy gaming have been the Fund's main foresight techniques so far, though other tools have been complementary. Accordingly, section III focuses on the scenario planning by illustrating applications before detailing the methods we have been using, while section IV describes policy gaming including the matrix policy gaming approach with which we have experimented so far. Section V summarizes the key points. In so doing, the note extends an invitation to those in the economics and finance fields (e.g., researchers, policymakers) to incorporate strategic foresight in their analysis and decision making.